Courtly riddles : enigmatic embellishments in early Persian poetry - Seyed-Gohrab, A. A. (Ali Asghar), 1968- (Iranian studies series (Leiden, Netherlands), 2010)
This book is the first study of Persian literary riddles to appear in English, analysing a wide range of complex riddling poems systematically from the tenth to the twelfth century. In addition to the genre of riddles, the book examines the relationship between metaphors and riddles and the genre of literary description. Riddles belong to the oldest genre in many literary traditions. O amber-bodied idol, precious ruby! You are fire with ambergris smoke, amber with fiery smoke; You have silver in your heart, red sulfur in your mouth; You have a snake in your throat, its teeth are on your tongue. You are the sun, burning the heaven, a meteor whose throne is the moon, fenugreek bearing flowers, a reed bearing tulips. A silver chain is wrapped around your golden feet, on your head is a sun composed of a single brilliant ruby. Riddles were composed at courts in the Iranian world for various purposes, such as highlighting the courtly insignia that refer to the ruler's administrative and military power. The aesthetic of puzzlement was much appreciated at courts. Through a riddle, the poet aims to demonstrate his artistic accomplishment in a short space; and at the same time he secures his social, professional and personal position at the court and in cultured circles. Literary riddles occur in the early specimens of Persian literature from the tenth century and they continue to be used in modern Iranian society.